Analysis of shoreline changes in Brondong District, Lamongan Regency, East Java, Indonesia - Kusumaningtyas, Al Izzha; Noverma; Perdanawati, Rizqi Abdi (Journal of Marine Resources and Coastal Management, 2026)
Brondong District in Lamongan Regency is one of Indonesia’s coastal zones where shoreline dynamics are highly sensitive to both natural processes and human activities. As coastal development intensifies, shoreline positions in this region exhibit periodic shifts, resulting in either land expansion or loss. Understanding these changes is critical for effective coastal management, regional planning, and risk mitigation. This study analyzed shoreline displacement from 1993 to 2019 and projected shoreline conditions up to 2030. Remote sensing techniques, supported by the Digital Shoreline Analysis System (DSAS), were employed to quantify shoreline movement and calculate accretion and erosion rates through transect-based statistical models. Land-use changes were analyzed using the regional spatial plan and Landsat imagery, validated through field observations. Results indicate that Brondong District experienced predominantly accretional shoreline movement over the study period. Brondong Village showed the most substantial accretion, with an average shoreline shift of 376.12 meters and an annual rate of 14.49 meters, while Lohgung Village exhibited the lowest, with 31.72 meters and 1.22 meters per year. Differences between villages suggest that local geomorphology, sediment supply, and human activities significantly influence coastal change. Projections for 2030 indicate that accretion will continue to dominate, with Brondong Village expected to experience an additional 42.58 meters of shoreline advance at an annual rate of 3.87 meters. Although the projected rate is lower than historical values, continued land accumulation highlights the long-term influence of sediment deposition, tidal processes, and coastal infrastructure. These findings provide valuable insights for sustainable coastal management, planning, and adaptation strategies in rapidly developing coastal zones.